Early goal directed mobility in the ICU: ‘something in the way you move’ - dos Santos, Claudia C.; Herridge, Margaret; Batt, Jane (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
In the March issue of Critical Care Medicine, Hodgson and colleagues from the Australian and New Zealand Intensive Care Society (ANZICS) Clinical Trials Group, published a multicenter pilot randomized controlled trial (RCT) conducted across international ICUs to evaluate the feasibility of implementing early goal directed mobility (EGDM) to achieve active exercises early during the ICU stay using a mobility team (1).